2019
DOI: 10.1016/j.celrep.2019.07.025
|View full text |Cite
|
Sign up to set email alerts
|

A CEP104-CSPP1 Complex Is Required for Formation of Primary Cilia Competent in Hedgehog Signaling

Abstract: Summary CEP104 is an evolutionarily conserved centrosomal and ciliary tip protein. CEP104 loss-of-function mutations are reported in patients with Joubert syndrome, but their function in the etiology of ciliopathies is poorly understood. Here, we show that cep104 silencing in zebrafish causes cilia-related manifestations: shortened cilia in Kupffer’s vesicle, heart laterality, and cranial nerve development defects. We show that another Joubert syndrome-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(97 citation statements)
references
References 89 publications
(158 reference statements)
6
91
0
Order By: Relevance
“…Recent work has reported Hedgehog (Hh) signaling defects in cell lines with dysfunction of the JBTS genes CEP104, CSPP1, and Armc9 (33,39). Therefore, we tested whether TOGARAM1 dysfunction leads to attenuated ciliary SMO accumulation in response to Hh stimulation in the engineered TOGARAM1-mutant hTERT-RPE1 cells described above (Supplemental Figure 5).…”
Section: Togaram1 Dysfunction Results In Attenuated Smo Translocationmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent work has reported Hedgehog (Hh) signaling defects in cell lines with dysfunction of the JBTS genes CEP104, CSPP1, and Armc9 (33,39). Therefore, we tested whether TOGARAM1 dysfunction leads to attenuated ciliary SMO accumulation in response to Hh stimulation in the engineered TOGARAM1-mutant hTERT-RPE1 cells described above (Supplemental Figure 5).…”
Section: Togaram1 Dysfunction Results In Attenuated Smo Translocationmentioning
confidence: 99%
“…To identify direct binding partners, we employed full-length ARMC9 and four fragments ( Figure 1A) as bait in a GAL4-based yeast two-hybrid (Y2H) interaction trap screen of two validated prey retinal cDNA libraries that were generated via random or oligo-dT primers (37). Using full-length ARMC9 as a bait, we identified four proteins previously implicated in ciliary function as binary interactors, including ARMC9 itself (suggesting a propensity to multimerize), TOGARAM1 (29,34), CCDC66 (36,38), and the JBTS-associated protein CSPP1 (39). Validation of these interactions and evaluation of the interacting domains was performed by Y2H co-expression.…”
Section: Identification Of a Novel Protein Module Implicated In Jbtsmentioning
confidence: 99%
See 2 more Smart Citations
“…CSPP1 interacts with centrosomes and microtubules and plays a role in cell‐cycle progression and spindle organization 28 . In vivo and in vitro analyses showed that CSPP1 directly interacts with CEP104 , which is required for the formation of Hedgehog signaling‐competent cilia, defects in which underlie Joubert syndrome 29 . Mutations in this gene were identified in patients with Joubert syndrome 21, which is an AR disorder characterized by CVH, elongated superior cerebellar peduncles, and deepened interpeduncular fossa, which together are recognized as the “molar tooth sign” on brain MRI 30 .…”
Section: Discussionmentioning
confidence: 99%